Successful Aging in Societies of Long Living: The Model of Selection, Optimization, and Compensation. - Lang, Frieder; Rohr, Margund (International Encyclopedia of the Social and Behavioral Sciences, 2015)
The processes and outcomes of successful aging are viewed in a life-span developmental perspective that emphasizes adaptive person-environment transactions across adulthood and the maximization of gains while minimizing losses. The chapter is organized around three questions: (a) What is successful aging?, (b) How is successful aging different from normal or pathological aging?, and (c) What are processes that lead to successful aging? - The model of selection, optimization, and compensation (SOC) points to a standard of optimality in successful life management in old age.
Keywords: Adaptation; Compensation; Gain-loss-dynamics; Health; Life-span psychology; Optimization; Optimality; Plasticity; Proactivity; Successful aging; Selection; SOC; Well-being